(untitled) (Journal of Computational Mathematics, 2002)
We present a class of relaxed asynchronous parallel multisplitting iterative methods for solving the linear complementarity problem on multiprocessor systems, and set up their convergence theories when the system matrix of the linear complementarity problem is an H-matrix with positive diagonal elements.